"A Study of Impact of Digitalization on Sales Employees" - Prof. Prabha Kumari, Prof. Dr. M.K. Singh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Digital technologies are the path breaking technologies making inroads in almost every sector we know about. Digitalization is prevalent across all industries changing the course of the future. The works aims to study the aspects of digitalization affecting the sales employees in the food and beverage service industry. The study is done on the sales employees of a cafe chain based out of Pune city, to study the effect of digitalization, both on professional and personal front. The sales employees are studied using observations and interviews to know the implications of digitalization on them. Significant impact was found on the sales employees, reflecting in both their professional and personal lives giving rise to sustainability concerns. Resorting to the Job Demands - Resources Model, the demands and resources could be segregated. Thus, leading to the path of discovery of possible solutions to the challenges arising out of digitalization in the realm of Human Resources Management.